IMPLEMENTATION OF LEGAL CERTAINTY PRINCIPLE AND ECONOMIC ANALYSIS OF LAW REGARDING ONLINE SERVICES OF DEMOGRAPHIC ADMINISTRATION IN BANDAR LAMPUNG IN IMPLEMENTING AN ELECTRONIC BASED GOVERNMENT SYSTEM - Ragani, Sondika; Rompis, Adrian; Amirullah, Muhamad (Cepalo, 2023)
Establishing a regulation regarding information and electronic transactions (ITE), which aims to develop Information Technology, can be carried out optimally, evenly, and spread to all levels of society to educate the nation's life. Establishing an Electronic-Based Government System (SPBE) aims to realize clean, effective, transparent, accountable governance, quality, and reliable public services. The Lampung Provincial Government has made a policy regarding implementing Population Administration. Still on the other hand, the Lampung Provincial Government still needs to provide facilities and infrastructure to improve the quality of population administration services online, both at the provincial and Bandar Lampung City levels. This contradicts the principles, goals, and ideals of the ITE Law and the SPBE. This study uses the Normative Empirical method. The results of this study indicate that the principle of legal certainty in the online Population and Civil Registration Administration Services in Bandar Lampung City has not been implemented as evidenced by the absence of a regulation regarding facilities and infrastructure to support population administration services and civil registration via online and the services provided have not provided satisfaction towards the people of Bandar Lampung City.